Diazepam and Tests of Thyroid Function. Issue 5749 (13th March 1971) - Clark, Frederick; Hall, Reginald; Ormston, Brian J.
Abstract : The effect of diazepam on thyroid function tests was examined in 12 euthyroid patients requiring the drug for psychiatric reasons and in six patients with thyrotoxicosis. Assessment was made before and after four weeks' therapy. There was no significant difference in results from tests of thyroid iodide trapping and binding (thyroid radioiodine uptake, thyroid clearance, and absolute iodine uptake) except in the one-hour thyroid uptake in the euthyroid group, which was increased after diazepam. This increase occurred without alteration in serum thyroid stimulating hormone levels. No change occurred in either group in tests of thyroid hormone release (protein-bound iodine, T-3 resin uptake, or Thyopac-3 and free thyroxine index). Patients with suspected thyroid disease who are taking diazepam do not need to stop therapy while their thyroid status is being determined.